Ruang-ruang Keadilan bagi Sang Margin - Kurniawan, Danang (Indonesian Journal of Theology, 2019)
This essay examines just space(s) from the perspective of Christian hospitality towards the marginalized. The focus for Letty Russell in her theology addresses those considered the â€˜unfortunateâ€™ or those victimized by the variegated visage of injustice (the â€˜unfairâ€™) as that face is set against â€˜the outsidersâ€™; Miroslav Volf focuses on the â€˜other,â€™ as does Amos Yong concerning â€œthe stranger.â€ Nevertheless, they use these three terms interchangeably. To build just space(s) for the marginalized, I intend to approach the justice discourse via two arguments: first, by claiming that every theory of justice derived philosophically tends to get trapped in matters of techno-calculation; second, by proposing the relevance of a theological approach for â€œpatchingâ€ such philosophical shortcomings. Following the parable of the workers in the vineyard in Matthew 20:10-16, we see that a theological approach yields a conceptualization of generosityâ€”as the commentaries of Michael Green showâ€”thereby demonstrating the relevance of such theological praxis. As a study in Christian hospitality, this essay proposes several ethical tenets for the building of just space(s) as spaces for justice that take as their point of departure the very same marginalized toward whom these spaces are oriented.